2014
DOI: 10.1186/bcr3676
|View full text |Cite
|
Sign up to set email alerts
|

Novel serum protein biomarker panel revealed by mass spectrometry and its prognostic value in breast cancer

Abstract: IntroductionSerum profiling using proteomic techniques has great potential to detect biomarkers that might improve diagnosis and predict outcome for breast cancer patients (BC). This study used surface-enhanced laser desorption/ionization time-of-flight (SELDI-TOF) mass spectrometry (MS) to identify differentially expressed proteins in sera from BC and healthy volunteers (HV), with the goal of developing a new prognostic biomarker panel.MethodsTraining set serum samples from 99 BC and 51 HV subjects were appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 36 publications
1
68
1
1
Order By: Relevance
“…Previous studies have reported 4.3, 8.1 and 8.9 kDa proteins as biomarkers of BC; however, these results differ to those of the present study (8,11,22,26). A 3.8 kDa protein, close to m/z 3,972, was reported to be highly sensitive for the diagnosis of BC by Chung et al (12). A number of serumbased candidate biomarkers have been identified in different studies (8,10,22,31).…”
Section: Peak Intensity Protein Peaks -------------------------------contrasting
confidence: 57%
See 1 more Smart Citation
“…Previous studies have reported 4.3, 8.1 and 8.9 kDa proteins as biomarkers of BC; however, these results differ to those of the present study (8,11,22,26). A 3.8 kDa protein, close to m/z 3,972, was reported to be highly sensitive for the diagnosis of BC by Chung et al (12). A number of serumbased candidate biomarkers have been identified in different studies (8,10,22,31).…”
Section: Peak Intensity Protein Peaks -------------------------------contrasting
confidence: 57%
“…Previous studies have reported a number of potential serum biomarkers that may be used to diagnose BC; BC1 (4.3 kDa), BC2 (8.1 kDa) and BC3 (8.9 kDa) (8,9 are as follows: BC1, inter-α-trypsin inhibitor heavy chain H4; BC2, C3a des-arginine-C terminal truncated peptide; and BC3, C3a des-arginine (10). A number of other potential biomarkers have been identified and demonstrated to have high diagnostic accuracy (7,11,12). However, validating these proteins is difficult due to different protocols for sample handling, patient populations and tumor characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The histological diagnosis of NSCLC patient #4 (with 35 years of smoking history) was squamous cell carcinoma; while the histological diagnosis of #1, #2, and #3 patients (nonsmokers) of NSCLC was adenocarcinoma (Supplemental Table S1). DISCUSSION Extensive effort has been expended on method development for analyzing the serum/plasma proteome to identify potential biomarkers (1,3,26,27). In the current study, we have developed a robust workflow combining PTM motif antibody enrichment and LC-MS/MS analysis for profiling different PTMs.…”
Section: Fig 2 Functional Classification Of Functions Of Proteins Imentioning
confidence: 99%
“…56 Despite the rapid evolution of MS-based proteomics methods, in terms of resolution power, mass accuracy, accurate quantification, and sequencing speed, together with parallel improvements in bioinformatics tools for analysis of large amounts of data, SELDI-TOF-MS we referred, popularly used in the first decade of 2000, still has a great impact on cancer proteomics to uncover crucial molecular events that drive malignant cells progression or response to therapy in recent years, and could pave the way for the identification of new therapeutic targets with higher sensitivity and resolving power. [57][58][59][60] Apolipoproteins (Apo-) bind lipids to form lipoproteins that transport these lipids through the lymphatic and circulatory systems. Serum and plasma lipoprotein metabolism are regulated and controlled by specific Apo-constituents of various lipoprotein classes, such as apoA-I, apoC-I, apoC-III, apo-H (b 2 glycoprotein), and others.…”
Section: Discussionmentioning
confidence: 99%